Histological scoring of immune and stromal features in breast and axillary lymph nodes is prognostic for distant metastasis in lymph node‐positive breast cancers. (8th January 2018) - Grigoriadis, Anita; Gazinska, Patrycja; Pai, Trupti; Irhsad, Sheeba; Wu, Yin; Millis, Rosemary; Naidoo, Kalnisha; Owen, Julie; Gillett, Cheryl E; Tutt, Andrew; Coolen, Anthonius CC; Pinder, Sarah E
Abstract: The prognostic importance of lymph node (LN) status and tumour‐infiltrating lymphocytes (TILs), is well established, particularly TILs in triple negative breast cancers (TNBCs). So far, few studies have interrogated changes in involved and uninvolved LNs and evaluated if their morphological patterns add valuable information for the prediction of disease progression in breast cancer. In a cohort of 309 patients enriched for TNBCs (170/309), we histologically characterised immune and stromal features in primary tumours and associated involved and uninvolved axillary LNs on routine haematoxylin and eosin stained sections. Of the 309 patients, 143 had LN‐positive disease. Twenty‐five histopathological features were assessed, including the degree of TIL presence, quantitative and qualitative assessment of germinal centres (GCs) and sinus histiocytosis. Multivariate and cross‐validated proportional hazard regression analyses were used to identify optimal covariate sets for prediction of distant metastasis‐free survival (DMFS). The degree of intratumoural and peritumoural immune infiltrate was associated with architectural changes in both uninvolved and involved LNs. By including clinicopathological characteristics as well as tumour and LN histopathological features in L2‐regularised proportional hazard models, the prediction of 5‐year DMFS was improved by 3–15% over the baseline in all cancers and in TNBCs. In LN‐positive cancers, the combination of Salgado's classification, lymphocytic lobulitis, size and number of GCs in the uninvolved LNs and location of GCs in the involved LNs carried significant prognostic information. From these features, a multivariate cross‐validation‐stable risk signature was constructed, which identified low‐risk groups within both LN‐positive breast cancers and the LN‐positive TNBCs group with a 10‐year DMFS probability of 78 and 87%, respectively. This study illustrates that, by incorporating histopathological patterns of involved and uninvolved LNs combined with primary tumour immune and stromal features, the prediction of developing distant metastasis in LN‐positive breast cancers can be estimated more accurately.